PENGARUH PERPUTARAN KAS, PERPUTARAN PERSEDIAAN, PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Asbi Amin (AkMen JURNAL ILMIAH, 2015)
The purpose of this study was to analyze the influence of cash turnover, inventory turnover and sales growth turnaround company to return on assets (ROA) at a food and beverage company. Population of this research is the food and beverage companies listed on t he Indonesia stock exchange (IDX) in year 2012-2014. Sampling method used is the purposive sampling and retrieved 13 companies as samples. Methods of analysis used is multiple regression analysis. Based on the results of partial or test T, cash turnover variable, inventory turnover and sales growth is not significant effect on profitability.